2020
DOI: 10.1002/jcp.29479
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of N‐TiO2 nanoparticle and its photo‐activated form on autophagy and necroptosis in human melanoma A375 cells

Abstract: The manipulation of autophagy provides a new opportunity for highly effective anticancer therapies. Recently, we showed that photodynamic therapy (PDT) with nitrogen‐doped titanium dioxide (N‐TiO2) nanoparticles (NPs) could promote the reactive oxygen species (ROS)‐dependent autophagy in leukemia cells. However, the differential autophagic effects of N‐TiO2 NPs in the dark and light conditions and the potential of N‐TiO2‐based PDT for the treatment of melanoma cells remain unknown. Here we show that depending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 80 publications
(190 reference statements)
0
27
0
Order By: Relevance
“…Another path to trigger AACD was recently reported ( 170 ). Whereas N‐TiO 2 -PDT induces efficient autophagic flux in the dark condition, its photo‐activation compromises pro-survival autophagy.…”
Section: Pdt-mediated Autophagy Regulation In Tumor Cellsmentioning
confidence: 94%
See 4 more Smart Citations
“…Another path to trigger AACD was recently reported ( 170 ). Whereas N‐TiO 2 -PDT induces efficient autophagic flux in the dark condition, its photo‐activation compromises pro-survival autophagy.…”
Section: Pdt-mediated Autophagy Regulation In Tumor Cellsmentioning
confidence: 94%
“…Some reports have shown that depending on the stress level, the autophagic apparatus might intrinsically contribute to other cell death programs, like apoptosis or necroptosis ( 35 , 56 , 59 , 62 , 104 , 128 , 141 , 144 , 145 , 147 , 155 , 166 170 ), see Table 2 . In spite of not inducing cell death per si , the RCD routine autophagy-mediated cell death (AMCD) may be significantly rescued by chemical autophagic inhibition (e.g.…”
Section: Pdt-mediated Autophagy Regulation In Tumor Cellsmentioning
confidence: 99%
See 3 more Smart Citations